Analysis of Science Literacy Using Test of Scientific Literacy Skills (TOSLS) in Science Teacher Candidate Students - Muhammad Azzarkasyi; Yusrizal Hasja; Jalaluddin; Junaidi; Ibrahim (Postgraduate, University of Mataram, 2025)
This study aims to analyze the ability of science literacy in science teacher candidates using the Test of Scientific Literacy Skills (TOSLS). This study uses descriptive quantitative research design. Sampling using random sampling technique on Science Study Program students with the number of students sampled as many as 60 people. The instrument used is a test tool for scientific literacy skills developed by the author with reference to the indicators contained in the development of the TOSLS test as many as 39 questions. The results showed that the indicator of understanding the investigation that leads to scientific knowledge was in the simply category with the interpretation of the average score obtained of 62.69, and the indicator of organizing, analyzing, and interpreting quantitative data and scientific information was in the simply category with the interpretation of the average score of 60.89. Meanwhile, when viewed based on the distribution of the number of respondents, 3% were found in the very good category, 34% in the good category, 43% in the sufficient category, 17% in the insufficient category, and 3% in the very insufficient category. Based on the results of the study, it can be concluded that prospective science teacher students already have science literacy skills in accordance with the good and simply categories, although there is one competency that is still less, namely in reading and interpreting graphical representations of data.